Quasi-Hexagonal VO2/Ag3VO4 Microcrystals for Photo-Catalytic Degradation of Rhodamine B - Tao1, Xiucheng; Hong1, Qing; Wu1, Tianqing; Liao2, Fan (Asian Journal of Chemistry, 2014)
Quasi-hexagonal VO2/Ag3VO4 heterogeneous photocatalyst was successfully synthesized via a hydrothermal method. Detailed characterization was carried out based on X-ray powder diffraction pattern, scanning electron microscopy, UV-visible diffuse-reflectance spectroscopy. The as-prepared samples exhibited strong absorption in the UV-light region and displayed excellent UV-light-driven photocatalytic activities and stabilities in degradation of Rhodamine B under UV-light irradiation (l = 400 nm). This enhanced photocatalytic activity might be attributed to the heterogeneous structure.